Innovative behavior in startups: An empirical study - Marisa Leal; Carmem Pereira Leal; Rui Silva (Administrative Sciences, 2023)
Considering the SECI model, which emphasizes a modern conception of knowledge management, the main objective of this study is to understand how the socialization, externalization, combination, and internalization (SECI) dimensions can influence innovative behavior within organizations. The quantitative method was adopted, carrying out a descriptive-correlational study in which 247 individuals participated. For data collection, a questionnaire was used. Their analysis was performed using SPSS software. The results show that of the four dimensions of the SECI model, only three have a positive influence on innovative behavior: externalization, combination, and internalization. This study highlights the importance that the SECI model has in understanding knowledge generated by companies/organizations, in particular, startups. It is possible to state that this model is extremely important to understand innovative behavior in startups, but also issues related to entrepreneurship, thus rendering this study into a guiding reference for companies.
Keywords: 350; co-incubation theory; innovative behavior; SECI model; social capital theory; startups